Accumulation of soil organic carbon after cropland conversion to short‐rotation willow and poplar. Issue 8 (7th February 2017) - Georgiadis, Petros; Vesterdal, Lars; Stupak, Inge; Raulund‐Rasmussen, Karsten
Abstract: The demand for bioenergy has increased the interest in short‐rotation woody crops (SRWCs) in temperate zones. With increased litter input and ceased annual soil cultivation, SRWC plantations may become soil carbon sinks for climate change mitigation. A chronosequence of 26 paired plots was used to study the potential for increasing soil organic carbon (SOC) under SRWC willow and poplar after conversion from cropland (CR) on well‐drained soils. We estimated SOC stocks in SRWC stands and adjacent CR and related the difference to time since conversion, energy crop species, SOC stock of the adjacent CR (proxy for initial SOC of SRWC) and the fine soil percentage (<63 μm) (FS). Soil cores to 40 cm depth were sampled and separated by layers of fixed depths (0–5, 5–10, 10–15, 15–25 and 25–40 cm). Additionally, soils were sampled from soil pits by genetic horizons to 100 cm depth. Comparisons of SOC stocks by equivalent soil masses showed that mean SOC stocks in SRWC were 1.7 times higher than those of CR in the top 5 cm of the soil ( P  < 0.001). The differences between SRWC and CR remained significant for the plough layer (0–25 cm) by a factor of 1.2 ( P  = 0.003), while no changes were detectable for the 0–40 cm ( P  = 0.32), or for the entire 0–100 cm soil layer ( P  = 0.29). The SOC stock ratio, that is the ratio of SOC stock in SRWC relative to CR, did not change significantly with time since conversion, although there was a tendency to an increase over time for the top 40 cm ( P  = 0.09). The SOC stock ratio was negatively correlated to SOC in CR and FS percentage, but there was no significant difference between willow and poplar at any depth. Our results suggest that SOC stocks in the plough layer increase after conversion to SRWC. Abstract : We evaluated whether cropland conversion to short‐rotation woody crops (SRWCs) may provide a sink for soil carbon, thus contributing to climate change mitigation. We used a chronosequence of 26 paired plots (adjacent cropland used as proxy for initial SOC in SRWC) to determine the effect on SOC stock of land‐use change from cropland to two different SRWC species, willow and poplar. Results showed that the SOC stocks corrected by equivalent soil masses were 1.7 times higher in SRWC compared to cropland in the top 5 cm ( P  < 0.001) and 1.2 times higher in the top 25 cm ( P  = 0.003). No changes could be detected in 0–40 cm ( P  = 0.32), or 0–100 cm ( P  = 0.29). The SOC stock ratios for SRWC vs. cropland did not change significantly with time since conversion, but were negatively correlated to SOC in cropland and fine soil percentage. There was no significant difference between willow and poplar at any depth.